Furniture Industry in Kenya : Situational Analysis and Strategy - Creapo Oy; World Bank Group (World Bank, Washington, DC, 2015)
The Government of Kenya recognizes that the performance of the furniture sector is crucial both to employment and growth in the country. The Ministry of Industrialization and Enterprise Development (MOIED) therefore requested an analysis of both the furniture and timber sectors, in order to understand their current state of development, their main constraints, and the interventions necessary to accelerate their growth. The objective of this report is to provide a comprehensive value-chain analysis of the Kenyan furniture industry, including the timber sub-sector, in order to assess policy options available to the MOIED and recommend critical interventions to stimulate the industry’s development. By situating Kenya’s furniture industry within the global and regional context, this paper also aims to identify ways in which to boost Kenya’s competiveness in the East African markets and beyond. The analysis in this report is largely focused on the wooden furniture sector (versus plastics, composites, and other furniture). The bulk of Kenya’s furniture industry is focused on wood, and Kenya has a competitive advantage in wood relative to South Africa, Asian countries, and Europe, which have very competitive value chains in furniture made from other materials.